2013
DOI: 10.1111/jpc.12141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three paediatric weight estimation methods in Singapore

Abstract: Of the three methods we evaluated, the BL tape method provided the most accurate and precise weight estimation for Singapore children. The APLS and Luscombe formulae underestimated and overestimated the children's weights, respectively, and were considerably less precise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 22 publications
8
29
0
Order By: Relevance
“…Reliability of Broselow Luten tape differs betweeen different populations and its accuracy has never been evaluated in Turkish children 12,13,[21][22][23][24] . Our results showed that Broselow Luten emergency tape can be reliably used in Turkish children with average weight and height.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability of Broselow Luten tape differs betweeen different populations and its accuracy has never been evaluated in Turkish children 12,13,[21][22][23][24] . Our results showed that Broselow Luten emergency tape can be reliably used in Turkish children with average weight and height.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported underestimations of actual weight with weight estimation tools due to overweight 2 27. To overcome this problem, some methods that reflect body habitus have been developed 15 16.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Singapore of 875 children had a favorable weight estimation than other two methods (Advanced Paediatric Life Support and Luscombe formulae). [16] The Broselow tape showed less of a difference with the actual weight in terms of mean percentage compared with the Pediatric Advanced Weight-Prediction in the Emergency Room and the Luscombe tape (+0.6% vs. +7.6% vs. -7.4%, respectively). To improve the quality of these tapes or our card, it may be necessary to adjust for the body habitus.…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies may have different outcomes, both favorable and unfavorable. [10][11][12][13][14][15][16] A study from India showed that the Broselow card may be useful for children with body weight of less than 10 kg. [11] The agreement percentage dropped from 70.8% to 56.3% if children weighed over 10 kg.…”
Section: Discussionmentioning
confidence: 99%